Isolation and Characterization of Streptomycetes with Potential to Decompose Organic Compounds During Bioremediation of Arable Soil - Ekenwosu Joseph Ugochukwu; Peter Ugochukwu Okorie (Sustinere: Journal of Environment and Sustainability, 2020)
The study has an objective of isolating and characterizing suspected Streptomycetes with the potential to decompose organic compounds in arable soil. The isolates were grown on a culture media and a total of 61 slopes were inoculated and labeled using the following characterization tests: catalase test, gram staining, oxidase test, motility test, and oxidative-fermentative test. After characterization tests, data generated in the laboratory were analyzed and the study showed that isolates A2 (c, e), B2 (c), C1 (b), C2 (a), D1 (e) and D2 (d) were suspected to be Streptomycetes species. Isolates D1 (d) and D2 (b) were suspected to be Escherichia coli while isolates A1 (a), B2 (a, b) and D1 (a) were suspected to be Bacillus species. Isolates A1 (b), C1 (a), D1 (c), D2 (e) were suspected to be Pseudomonas species. Further identification showed that isolates A2 (d) and B1 (b) could be Enterobacter species while isolates A2 (a, b) were suspected to be Klebsiella species. The study tentatively identified Streptomycetes species; Escherichia coli; Bacillus species; Enterobacter species; Pseudomonas species and Klebsiella species. The suspected Streptomycetes identified were considered as potential organic matter decomposers in arable soil.